2008
DOI: 10.1007/s10495-008-0273-y
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by withaferin A in human leukemia U937 cells through down-regulation of Akt phosphorylation

Abstract: Withaferin A, a major chemical constituent of Withania somnifera, has been reported for its tumor cell growth inhibitory activity, antitumor effects, and impairing metastasis and angiogenesis. The mechanism by which withaferin A initiates apoptosis remains poorly understood. In the present report, we investigated the effect of withaferin A on the apoptotic pathway in U937 human promonocytic cells. We show that withaferin A induces apoptosis in association with the activation of caspase-3. JNK and Akt signal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 36 publications
6
114
0
Order By: Relevance
“…We found that SR141716 is an effective tumor cell growth inhibitor, displaying IC50 values of 13 and 18 M in Jurkat and U937 cells, However, if the quiescent status (G 0 /G 1 block) was likely to make PBMC quite resistant to SR141716-triggered death stimuli, the same G 0 /G 1 block induced in U937 by SR141716 delayed, but did not prevent subsequent cell death. A possible explanation of the different capabilities of U937 cells and PBMC to counteract SR141716 cell death-promoting activity might lie in the different effects of the drug on PI3K/AKT pathways, known to contribute to apoptosis-resistance [37][38][39]. In PBMC, SR141716 was found to increase the levels of pAKT [19], while here we showed that in U937 cells the drug decreased, as early as 4 h following treatment, the level of pAKT as compared to untreated controls.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…We found that SR141716 is an effective tumor cell growth inhibitor, displaying IC50 values of 13 and 18 M in Jurkat and U937 cells, However, if the quiescent status (G 0 /G 1 block) was likely to make PBMC quite resistant to SR141716-triggered death stimuli, the same G 0 /G 1 block induced in U937 by SR141716 delayed, but did not prevent subsequent cell death. A possible explanation of the different capabilities of U937 cells and PBMC to counteract SR141716 cell death-promoting activity might lie in the different effects of the drug on PI3K/AKT pathways, known to contribute to apoptosis-resistance [37][38][39]. In PBMC, SR141716 was found to increase the levels of pAKT [19], while here we showed that in U937 cells the drug decreased, as early as 4 h following treatment, the level of pAKT as compared to untreated controls.…”
Section: Discussionmentioning
confidence: 46%
“…Since the PI3K/AKT pathways are well-characterized cell survival signalling pathways that block apoptosis in a variety of cell types [37][38][39], we examined the role of PI3K-dependent signals in counteracting SR141716-induced cell death by means of a pharmacological approach. In preliminary experiments we found that the combined treatment with SR141716 and LY294002, a A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 selective P13K inhibitor, caused extensive cell death at 24 h. Thus, in subsequent experiments the effect of PI3K inhibition was quantified as early as 12 h after treatment (Fig.…”
Section: Pi3k/akt Pathway Has a Survival Role In Sr141716-induced Celmentioning
confidence: 99%
“…Previously, we reported that Wit A decreased the cell viability in a dose-dependent manner in U937 cells (Oh et al, 2008). In the present study, we investigated whether Wit A could potentiate IR-induced apoptosis.…”
Section: Wit a Enhances Ir-induced Apoptosis In U937 Cellsmentioning
confidence: 83%
“…In the present study, we investigated whether Wit A could potentiate IR-induced apoptosis. When we examined the effect of Wit A on the viability of U937 cells, 0.5 lM Wit A did not markedly alter the viability (Oh et al, 2008). But we found that treatment of U937 cells with subtoxic doses (0.5 lM) of Wit A and IR (10 Gy) can effectively induce cell death (Fig.…”
Section: Wit a Enhances Ir-induced Apoptosis In U937 Cellsmentioning
confidence: 96%
“…38 Bcl-2 is known to be a client protein of Hsp90. 39 Surprisingly, WA treatment did not reduce Bcl-2 levels in all of our DLBCL cell lines except SudHL-6 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%